Pengaruh Reward Dan Punishment Terhadap Kinerja Pegawai Negeri Sipil Pada Dinas Pemuda, Olahraga Dan Pariwisata Kabupaten Paser - Rusmiati Rusmiati; Achmad Aprianor Firdaus; Muhammad Fadil Falah (Master Manajemen, 2024)
The purpose of this research is to determine the influence of Reward (X1) and Punishment (X2) which influence jointly (simultaneously) and individually (partially) on the performance of Civil Servants at the Paser Regency Youth, Sports and Tourism Service. From the research results, it was obtained that the validity test results of the total number of questions were 22 items, all of which had a value of rcount > rtable, which means that all questions were valid (feasible). From the results of the reliability test, it can be seen that the results obtained were 0.881, which means that the questionnaire items can be said to be reliable because the Cronbach's Alpha value is > 0.6. From the research results of multiple linear regression analysis, the regression equation Y = 1.152 + 0.338 X1 + 0.383 X2 is obtained. The magnitude of the correlation coefficient (R) is 0.737, this shows that there is a strong relationship between the Reward variable (X1) and the Punishment variable (X2) on the Performance of Civil Servants (Y) at the Paser Regency Youth, Sports and Tourism Service. Meanwhile, the coefficient of determination (R2) is 0.543, which means that the Reward variable (X1) and Punishment variable (X2) can explain the Civil Servant Performance variable (Y) at the Paser Regency Youth, Sports and Tourism Service by 54.3% while the remaining is 45. 7% is influenced by other variables not studied. From the results of the F Test, it is obtained that Fcount is 18.432 > Ftable 3.30 so it can be concluded that there is a significant influence simultaneously (simultaneously) between the Reward variable (X1) and the Punishment variable (X2) on the Civil Servant Performance variable (Y) at the Youth Service, Sports and Tourism in Paser Regency so that the first hypothesis is confirmed or Ha is accepted and H0 is rejected. From the results of the t test for the Reward variable (X1) and the Punishment variable (X2) they have a significant effect on the Performance of Civil Servants (Y) at the Paser Regency Youth, Sports and Tourism Service. Furthermore, the results of the t test show that the Punishment variable (X2) has a dominant influence on Civil Servant Performance (Y) which is strengthened by the highest t value of 2.758 and the smallest significance value of 0.010 so that the second hypothesis is proven or Ha is accepted and H0 is rejected.